The Effect Of Teacher Performance On Learning Quality At Sdn Pasir Putih 02 - Putri, Nadia Ananda; Irawan, Bambang (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the effect of teacher performance on learning quality in a public primary school. Teacher performance is considered a crucial factor in determining the effectiveness of the learning process, including lesson planning, instructional implementation, classroom management, and evaluation. This research employed a quantitative approach using a survey method. The research subjects consisted of teachers and students at SDN Pasir Putih 02. Data were collected through validated questionnaires and analyzed using simple linear regression techniques. The results indicate that teacher performance has a significant effect on learning quality, as evidenced by a significance value of p < 0.05. The coefficient of determination shows that teacher performance contributes substantially to the improvement of learning quality. These findings emphasize the importance of enhancing teacher performance as a strategic effort to improve learning quality in primary education.